Factors Associated with Breast Cancer Risk According to Tumor Subtypes: Triple Negative Breast Cancer vs. NON-Triple Negative Breast Cancer Among Women in Karachi, Pakistan - Shamsi, Uzma; Shamsi, Azra; Usman, Shaeryar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate risk factors associated with triple negative breast cancer among women in Karachi Pakistan Study Design: Multicenter hospital-based case control study Place and Duration of Study: Aga Khan University Hospital and Karachi Institute of Radiation & Nuclear Medicine Karachi, Pakistan from February 2015 to July 2018. Methodology: There were three hundred and eighty cases of breast cancer patients who had complete molecular profiling and who were compared with 798 controls and in person interviews were conducted. Results: The multivariable multinomial logistic regression analyses showed that both triple negative breast cancer and non- triple negative breast cancer subtypes were associated with poor socioeconomic status and low Vitamin D concentrations with triple negative breast cancer risk much higher among women of low socioeconomic status (OR=8.76, 95% CI= 2.45, 31.32) and women with vitamin D deficiency (OR=3.11, 95%CI= 1.17. 8.29). Conclusions: Correction of Vitamin D deficiency in women maybe a possible cost-effective strategy to prevent triple negative breast cancer like aggressive breast cancer. It should be further tested though cohort studies or clinical trials in our population.